Improving HIV Treatment Adherence through a Public Private Partnership in Zambia - Fomundam, Henry; Maranga, Andrew; Kamanga, Joseph; Tesfay, Abraham; Choola, Tamara; Nyangu, Stephen; Wutoh, Anthony (Scientific Research, 2014)
Background: Effective ART with low viral loads and absence of STIs significantly reduce chances of sexual transmission of HIV. ART is therefore a key pillar in HIV prevention. Appropriate support is however essential for optimum treatment outcome, patient safety and HIV prevention benefit. The scale-up of ART continues to strain the already overstretched human resources in public facilities, impacts on the quality of care, and contributes to loss to follow-up. Task shifting is therefore a strategy to augment the limited human resources. Methodology: In partnership with the Livingstone General Hospital (LGH) and four private pharmacists, the COH III Project through Howard University is promoting quality HIV care by engaging the pharmacists in adherence counselling and treatment monitoring. The LGH ART pharmacist allocates consenting stable ART clients to pharmacies based on willingness to be referred and patient preference. Patients are given schedule of visits to pharmacies where the pharmacists provide medication/adherence counselling and monitor side effects. Patients with medication/treatment issues are referred back to the LGH ART clinic for follow-up. Results: Between October 2012 and August 2013, 280 patients were enrolled and followed up by the four pharmacists. 69% of patients visited the pharmacy at least once, 25% at least twice and 13% at least thrice. The 33 client referrals by pharmacists to LGH were related to adverse drug reactions, suspected treatment failure, pregnancy, and treatment monitoring. The intervention has reduced workload for the ART pharmacist; improved communication of treatment challenges and identification of patients with medication related problems, and reduced travel distances and waiting times. This has resulted in improved adherence and better patient outcomes. Conclusion: Private pharmacists present an opportunity to improve quality of HIV interventions in poor human resource capacity settings. The necessary legal and regulatory framework needs to however be developed to guide the process
Keywords: Public-Private Partnership; Adherence Support; Private Pharmacists; Treatment Monitoring; Human Resources Challenge